(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2019)
In recent years some previously hidden or ignored fields of media production and distribution have been mapped by many research efforts. Ethnographical methods (as participant observation and in-depth interviews) have been widely employed, together with production documents and promotional materials. Building on the international debate and on some investigations done in the field of contemporary Italian TV production and distribution, this essay wants to raise some methodological issues involving the data collection and the professionals-informants status. The intricacies of access, the effectiveness of involving the “middle-management” and the need to triangulate the sources will be especially addressed.